(untitled) (Journal of Electrical Engineering, 2011)
An analysis of highly birefringent optical fiber composed of a central elliptical hollow core with a circular cladding is carried out in this work using finite element method. High birefringence compare to that of the conventional solid elliptical core fiber is obtained. The birefringence properties in terms of various waveguide parameters, e.g., core ellipticity, ratio of hole size and core size, refractive index difference between core and cladding are calculated. The propagation properties, such as, group effective index, group birefringence, and polarization mode dispersion have also been calculated and their wavelength dependence are shown. It can be seen that the dispersion of this hollow core fiber is comparable to that of the conventional polarization maintaining fibers. Index Terms: Optical fiber; birefringence; finite element method; waveguide; dispersion; refractive index; polarization. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 10-15